Microbubble contrast agent SonoVue combined with oxytocin improves the efficiency of high-intensity focused ultrasound ablation for adenomyosis - Ruihong Yao (Taylor & Francis Group, 2021)
Background To investigate the combined enhancing effects of microbubble-contrast SonoVue and oxytocin on high-intensity focused ultrasound (HIFU) ablation of adenomyosis. Methods 330 patients with adenomyosis were randomly assigned to SonoVue and oxytocin group (group A, n = 82), oxytocin (group B, n = 85), SonoVue (group C, n = 81), or the control (group D, n = 82) for HIFU ablation. In group A, oxytocin was dripped 0.32 IU/min, and HIFU ablation was started one minute after SonoVue injection. In group B, oxytocin was dripped 0.32 IU/min during ablation. In group C, HIFU ablation was started one minute after SonoVue injection. In group D, neither oxytocin nor SonoVue was applied. The clinical data, treatment results, and complications were analyzed. Results All participants underwent HIFU treatment safely, and the mean energy efficiency factor (EEF) in the four groups was 4.7 ± 0.9J/mm3, 8.5 ± 0.6J/mm3, 8.9 ± 0.7J/mm3, and 12.6 ± 1.8J/mm3, respectively, with the mean ablation time (AT) of 633.7 ± 55.1 s, 874.2 ± 65.6 s, 936.3 ± 85.2 s, and 1103.2 ± 96.2 s, respectively. The non-perfused volume ratios (NPVR) were 90.4 ± 8.8%, 88.7 ± 9.1%, 89.4 ± 7.2%, 80.5 ± 7.9%, respectively. In addition, EEF and AT were the shortest in group A (p < 0.05). NPVR was significantly higher in group A than in the control group D (p < 0.05). The incidence rates of adverse events were not significantly different in the four groups (p > 0.05). Conclusions Compared to the control group, oxytocin combined with SonoVue in HIFU for adenomyosis can significantly decrease the energy and time needed for the ablation and safely enhance the treatment efficiency by improving the cavitation and heating of HIFU ablation and increasing the non-perfused volume ratio.